Political institutions, connectedness, and corporate risk-taking - Boubakri, Narjess; Mansi, Sattar A; Saffar, Walid (Journal of International Business Studies, 2013)
We investigate the impact of political institutions on corporate risk-taking. Using a large sample of non-financial firms from 77 countries covering the period from 1988 to 2008, we find that sound political institutions are positively associated with corporate risk-taking, and that this relation is stronger when government extraction is higher. In a subsample of 45 countries, we also find that politically connected firms engage in more risk-taking, which suggests that close ties to the government lead to less conservative investment choices. Our results are economically significant, and are robust to alternative risk-taking measures, various political institution proxies, cross-sectional and country-level regressions, and endogeneity concerns of political institutions. Our results have important implications for governments and corporate managers by providing direct relevance of political institutions to the corporate decision-making process. To encourage investment at the firm level, and hence innovation and overall growth, governments need to undertake the necessary reforms to control corruption and enforce contracts better, and thus decrease government predation and extraction.